Copyright for Instructors in World Laws and Conventions - Abdulwahab Al-Maamari (University of Science and Technology, Yemen, 2013)
Abstract The author of the faculty members in the universities and institutions of the higher education is he who collects the information in a manner of creative science, resulting in the addition of any new at any science. He has literary and physical rights for his book protected by the local laws and international conventions. These physical rights are such the copyright, right of translation, representation, public performance, public recitation, T.V, rights of cinema, modification, and tracking. However, the literary rights are such the rights of the author within the proportion of his book as the so-called the right of paternity, the right of the author in detecting his book, the right of the author in respecting his book, and preserve it from any interpolation or distortion, and the right of the author in rejecting any interpolation or distortion, or any amendment for his book, or any prejudice to his book affected the author or his honor.  The local laws and international conventions approve the lawful protection of the author's right since the moment he became creative and continues until his death and after. The right of the author should be transferred in the economic exploitation to his heirs according to the rules of pensions and awards of the service for thirty years as to be calculated by the 1st January in accordance with the Yemeni law. The international laws and conventions prohibit the infringement of the author's copyright whether total or partial infringement at any manner of infringement, which may be illegal copying or modification and distribution without the author's approval. All of that is included in the law protecting the Yemeni intellectual right comparing with the law protecting the Egyptian intellectual rights within the international conventions related.    Key words: Intellectual property rights, faculty member, law of intellectual property protection, TRIPs convention.